Evaluation of the percentage tissue altered as a risk factor for developing post‐laser in situ keratomileusis ectasia. Issue 7 (July 2017) - Saad, Alain; Binder, Perry S.; Gatinel, Damien
Abstract : Purpose : To assess the currently recommended percentage tissue altered (PTA) metric for its ability to screen for ectasia after laser in situ keratomileusis (LASIK). Setting : Gavin Herbert Eye Institute, University of California, Irvine, California, USA, and Rothschild Foundation, Paris, France. Design : Retrospective case series. Methods : The study used a LASIK database created by 1 surgeon for LASIK cases with normal preoperative topography that had a minimum follow‐up of 24 months with complete preoperative and intraoperative data to permit the calculation of PTA values to detect eyes at risk for developing ectasia. Results : Of the eyes, 593 eyes had complete data and met the inclusion criteria. Based on measured flap thickness, 126 eyes (21%) had a PTA value of 40% or more (mean 44) and a percentage of that flap thickness accounted for the PTA (mean 66.7%; range 34% to 92%). The mean attempted laser ablation was 79.8 μm ± 29.2 (SD), and the mean residual bed thickness was 304.4 ± 29.2 μm (range 212 to 369 μm). No eye developed ectasia over a mean follow‐up of 30 months. Conclusions : The current PTA calculation when applied to a LASIK population with normal preoperative topography and flap thickness measured with ultrasound did not predict the risk for ectasia. Differences between study populations and assumptions might have accounted for the different outcomes obtained in the initially published PTA study.